The evolution of HOM-C homeoboxes in the Dipteran family Drosophilidae. - DeSalle, R.; Branham, M.A.; O'Grady, P.; Gatesy, J. (Insect Molecular Biology, 2003)
Forty-five new Homeotic Complex (HOM-C) homeobox sequences from six species of Drosophilidae (Drosophila heteroneura, D. adiastola, Zaprionus vittiger, Chymomyza amoena, Scaptodrosophila pattersoni and Hirtodrosophila pictiventris) were obtained using a PCR-cloning method. These new homeoboxes are from the labial, proboscipedia, Deformed, Sex combs reduced, fushi tarazu, Antennapedia, Ultrabithorax, abdominal-A and Abdominal-B genes. Phylogenetic signal in the homeobox sequences was assessed and several aspects of sequence evolution were examined. In particular, codon bias was examined and found to exist between the drosophilid species examined here and Anopheles gambiae outgroup sequences. In addition, different patterns of codon bias were detected in homeoboxes interrupted with introns when compared to homeoboxes that are uninterrupted.